Age-specific risk of incident prostate cancer and risk of death from prostate cancer defined by the number of affected family members - Brandt, Andreas; Lorenzo Bermejo, Justo; Sundquist, Jan; Hemminki, Kari (European urology, 2010)
Background - The thorough assessment of familial prostate cancer (PCa) risk is as important as ever to provide a basis for clinical counselling and screening recommendations. - Objective - Our aim was to determine the age-specific risks of PCa and the risk of death from PCa according to the number and the age of affected first-degree relatives. - Design, setting, and participants - The nationwide Swedish Family-Cancer Database includes a record of >11.8 million individuals and their cancers from 1958 to 2006. All men from the database with identified parents (>3.9 million individuals) were followed between 1961 and 2006. The study included 26 651 PCa patients, of whom 5623 were familial. - Measurements - The age-specific hazard ratios (HRs) of PCa and the HRs of death from PCa were calculated according to the number and age of affected fathers and brothers. - Results and limitations - The HRs of PCa diagnosis increased with the number of affected relatives and decreased with increasing age. The highest HRs were observed for men <65 yr of age with three affected brothers (HR: approximately 23) and the lowest for men between 65 and 74 yr of age with an affected father (HR: approximately 1.8). The HRs increased with decreasing paternal or fraternal diagnostic age. The pattern of the risk of death from familial PCa was similar to the incidence data. - Conclusions - The present results should guide clinical counselling and demonstrate the vast increases in risk when multiple first-degree relatives are affected.
Gesehen am 08.02.2023